The Influence of Music on The Endurance of The Bandung Running Community - Yordhi Lesmana Putra; Tantra Paramitha, Sandey; Fitri, Mustika; Wahyudi, Agung (Universitas Muhammadiyah Kuningan, 2024)
This study aims to explore the influence of listening to music on running performance and endurance in the running community of Bandung City. The method used involves the utilization of Survey Monkey as an instrument to gather data from respondents through specifically designed online questionnaires. The questionnaire includes inquiries about the preferred time for running exercises, the type of music listened to, the duration and intensity of running, and the impact of music on the running experience. Additionally, a qualitative approach is employed as thematic analysis of respondents' responses to delve into their perceptions of the influence of music in the context of running. The results of this study reveal that the average age of respondents falls within the range of 18-45 years among 400 respondents, divided into 150 females and 250 males, with the majority being students. The majority of respondents run with a frequency of 40.00% per week. The timing of running exercises tends to be more dominant in the morning, reaching 72.50% of the total respondents. More than half of the respondents, 57.50%, use devices to listen to music while running. The majority of them, 73.98%, listen to pop music genres. Additionally, 47.37% of respondents are able to sustain a running duration of more than 30 minutes. These findings provide a better understanding of running exercise preferences and habits, as well as highlight the potential influence of music on the physical and mental activities of individuals in the running community.